Effect of Shoot Peening Air Pressure Variations on Hardness and Microstructure of ST-37 Material: Pengaruh Variasi Tekanan Udara Shoot Peening Terhadap Kekerasan dan Struktur Mikro pada Material ST-37 - Sukarno, Nota Ali; Samporno, Carolus Borromeus Krishna; Wibowo, Trio Nur (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
ST 37 material is a type of material that is easily available on the market at a relatively cheaper cost. However, the mechanical properties need to be improved so that they are better and have a longer life time. By using the shot peening method, it is hoped that changes in the shape of the microstructure will occur and the hardness value will increase. This research is focused on determining changes in microstructure and hardness values that occur as a result of the shot peening process with variations in air pressure of 2, 4, 6, and 8 kg/cm2. Shooting duration is 5 minutes. The diameter of the steel shot is 0.8 mm which has a hardness value of 40-50 HRC and the distance between the nozzle and the specimen surface is 100 mm. The microstructure was analyzed using an optilab microscope with 100 times magnification and photographed using an optilab connected to a computer. Surface hardness testing was tested using a micro Vickers hardness tester using an indentation load of 10 grams for 10 seconds. The research results show that a smoother microstructure layer is formed on the shot peened surface. The hardness test results indicate an increase in hardness proportional to the air pressure in the shot peening treatment method. Changes occurred in the raw material specimen with a hardness value of 187.14 VHN increasing to 194.20 VHN in the specimen with a shot pening air pressure of 2 kg/cm2. The increase in hardness tends to increase in proportion to the increase in shot peening air pressure, but is not very significant. Air pressures of 4, 6, and 8 kg/cm2 have hardness values of 199.41, 201.64, and 204.31 VHN. The data shows that the surface treatment method of shootpeening with varying pressure has had a positive impact in the form of increasing hardness in proportion to the increase in pressure.